Factors associated with modern contraceptive utilization among reproductive age women in Kenya; evidenced by the 2022 Kenyan demographic and health survey - Gosa Mankelkl; Altaseb Beyene Kassaw; Beletu Kinfe (BMC, 2024)
Abstract Background Globally, sexual and reproductive health is a significant public health issue for women of the reproductive age group. A modern contraceptive method enables individuals and families to manage fertility by reducing unintended pregnancies, abortions, pregnancy-related morbidity, and death. A modern contraceptive method is a drug or medical treatment that prevents sexual activity from leading to pregnancy. However, there is limited reliable and updated data on factors associated with modern contraceptive utilization among reproductive-age women at the national level in Kenya. So, the major goal of this study was to evaluate factors associated with modern contraceptive utilization among women of reproductive age in Kenya at the national level, as evidenced by the 2022 Kenyan demographic and health survey. Methods The most recent datasets from the Kenyan Demographic and Health Survey were used for secondary data analysis. In all, 14,987 women of reproductive age participated in the investigation. Data for multivariable analysis on the factors influencing modern contraceptive utilization among Kenyan women of reproductive age can be obtained from the Kenyan Demographic and Health Survey. Finally, the odd ratio and percentages were presented along with their 95% confidence intervals. Result This study includes a total weighted sample of 14,987 reproductive-age women from the Kenyan demographic and health survey. Of the total contraceptive use, 90.1% of the study participants used modern contraceptives. Being married [AOR: 1.593, 95% CI (1.302, 1.948)], living in an urban area [AOR: 1.230, 95% CI (1.060, 1.428)], reading a magazine [1.002, 95% CI (0.921, 1.091)], listening to radio [AOR: 1.265, 95% CI (1.101, 1.454)], not breastfeeding [AOR: 1.296, 95% CI (1.114, 1.507), and having more than two children [AOR: 2.350, 95% CI (1.603, 3.445)] were the factors that promote modern contraceptive utilization. Conversely, having a history of terminated pregnancy [AOR: 0.767, 95% CI (0.657, 0.897), being Muslim [AOR: 0.566, 95% CI (0.418, 0.766)], and being in the 35-39 age range [AOR: 0.766, 95% CI (0.605, 0.971)] were all associated with a lower use of modern contraceptives. Conclusion Certain factors such as marriage, living in urban areas, having more than two children, having a female-led household, belonging to the middle class, reading magazines, listening to the radio, and not breastfeeding have a positive correlation with the use of modern contraceptives. Conversely, being a Muslim, aged between 35 and 39, and having a history of miscarriages are negatively correlated with the use of modern contraceptives. This indicates that addressing socioeconomic, geographic, and cultural barriers could improve the effectiveness of modern contraceptive.